Risky Sexual Behavior and HIV/STI among Injecting Drug Users in India: Findings from Large-Scale Bio-Behavioral Surveys in Nagaland, Manipur and Maharashtra, India - Sharma, Santosh Kumar; Singh, Shri Kant; Talukdar, Bedanga (Journal of Population and Social Studies [JPSS], 2018)
Injecting Drug Users (IDUs) are vulnerable to sexually transmitted infections (STIs) and human immunodeficiency virus (HIV) as they are exposed to unsafe practices such as needle sharing and unprotected sex. This study utilized data from surveys conducted in India by Integrated behavioral and Biological assessment (IBBA) Phase 1 (2005-06) and Phase 2 (2009-10) in states having highest HIV/STIs prevalence. The study examines socio-demographic characteristics and factors of consistent condom use and consequential STI symptoms among IDUs and the results showed the mean age of IDUs has increased from 26 years to 29 years in the second round of survey. The IDUs are more likely to be unmarried, illiterate and unemployed in both surveys. Multivariate analysis revealed that IDUs in second round of IBBA were significantly 14 times more likely to started first injecting drug after two years of first drug use than the first round of IBBA. The IDUs who have a regular partner and share their needle or syringe were less likely in showing the consistency of condom use with multiple sex partners. Policy framework and interventions with a central focus on IDUs is vital as users above 30 years old who were illiterate and shared needle/syringes were likely to contract HIV.